Pengaruh Budaya Organisasi, Motivasi Dan Komunikasi Terhadap Kinerja Pegawai Dengan Semangat Kerja Sebagai Variabel Intervening Pada Dinas Pendidikan Dan Kebudayaan Kabupaten Sijunjung - Aidil Fitra; Marta Widian Sari; Ai Elis Karlinda (CV. ITTC INDONESIA, 2026)
The Influence of Organizational Culture, Motivation and Communication on Employee Performance with Work Spirit as an Intervening Variable at the Education and Culture Office of Sijunjung Regency, under the guidance of Mrs. Dr. Marta Widian Sari, S.E., M.M and Ai Elis Karlinda, S.E., M.M. This study aims to determine and try to analyze the Influence of Organizational Culture, Motivation and Communication on Employee Performance with Work Spirit as an Intervening Variable at the Education and Culture Office of Sijunjung Regency. This study is a Structural Equation Modeling (SEM) model with SmartPLS 3.0 analysis tools. The population and sample of this study are employees of the Education and Culture Office of Sijunjung Regency. The research results found a significant influence between organizational culture and work morale. Motivation and work morale also had a significant influence. Communication and work morale also had an insignificant influence. Organizational culture and employee performance also had a significant influence. Motivation and employee performance also had an insignificant influence. Communication and employee performance also had an insignificant influence. Morale and employee performance also had a significant influence. Morale mediated the relationship between organizational culture and employee performance. Morale mediated the relationship between motivation and employee performance. Morale did not mediate the relationship between communication and employee performance.